LITERATURE STUDY: APPLICATION OF PROBLEM BASED LEARNING (PBL) IN HIGH SCHOOL CHEMISTRY MATERIAL TO IMPROVE STUDENT LEARNING OUTCOMES - Emilia, Talitha; Auniillah, Fadia Hayya Tahta; Rahmawan, Setia (Jurnal Pembelajaran Sains, 2025)
This research aims to examine and describe using the Problem-based Learning (PBL) learning model as a strategy to improve chemistry learning outcomes. This qualitative research uses a literature review method, which involves searching previously published writings to find theoretical references related to the case or issue. The secondary data analysis method uses data on student learning outcomes in the chemistry course with a quantitative descriptive approach. Documentation, or tracing textual sources with various themes and issues mentioned, is the method used to collect data. Some of the data sources are books, online journals, the internet, conferences, research findings, and information related to study materials.